(untitled) (Swiss Medical Weekly, 2025)
Point-of-care ultrasound (POCUS) is a valuable addition to the diagnostic armamentarium of internal medicine specialists, improving patient assessment and treatment guidance. Early acquisition and continuous development of ultrasound skills during clinical training are key to maintaining the high quality of POCUS. In Switzerland, POCUS Component 1 (basics of emergency medicine ultrasound) of the Swiss Society of Ultrasound in Medicine (SGUM) postgraduate certification programme will be a mandatory component of board certification in General Internal Medicine (GIM) after 2026. Clinical institutions face the challenge of integrating POCUS teaching into daily practice. The following article addresses this challenge by describing the current regulatory conditions of POCUS training and presenting the POCUS training programme at Stadtspital Zürich Triemli as a blueprint for other postgraduate education sites in Switzerland.